Application of portable online LED UV fluorescence sensor to predict the degradation of dissolved organic matter and trace organic contaminants during ozonation. (15th September 2016) - Li, Wen-Tao; Majewsky, Marius; Abbt-Braun, Gudrun; Horn, Harald; Jin, Jing; Li, Qiang; Zhou, Qing; Li, Ai-Min
Abstract: This work aims to correlate signals of LED UV/fluorescence sensor with the degradation of dissolved organic matter (DOM) and trace-level organic contaminants (TOrCs) during ozonation process. Six sets of bench-scale ozonation kinetic experiments incorporated with three different water matrices and 14 TOrCs of different reactivity (group I ∼ V) were conducted. Calibrated by tryptophan and humic substances standards and verified by the lab benchtop spectroscopy, the newly developed portable/online LED sensor, which measures the UV280 absorbance, protein-like and humic-like fluorescence simultaneously, was feasible to monitor chromophores and fluorophores with good sensitivity and accuracy. The liquid chromatography with organic carbon detector combined with 2D synchronous correlation analysis further demonstrated how the DOM components of large molecular weight were transformed into small moieties as a function of the decrease of humic-like fluorescence. For TOrCs, their removal rates were well correlated with the decrease of the LED UV/fluorescence signals, and their elimination patterns were mainly determined by their reactivity with O3 and hydroxyl radicals. At approximately 50% reduction of humic-like fluorescence almost complete oxidation of TOrCs of group I and II was reached, a similar removal percentage (25–75%) of TOrCs of group III and IV, and a poor removal percentage (<25%) of group V. This study might contribute to the smart control of advanced oxidation processes for the water and wastewater treatment in the future. Graphical abstract: Highlights: A novel LED UV fluorescence sensor was developed towards online monitoring. Protein-like and humic-like fluorophores showed similar oxidation kinetics. MW changes of DOM was characterized by LC-OCD 2D synchronous correlation analysis. Removal of TOrCs was correlated with the decrease of LED UV fluorescence signals.